2020
DOI: 10.1002/lt.25798
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Spontaneous Portosystemic Shunts in Living Donor Liver Transplantation

Abstract: Earn MOC for this article: www.wileyhealthlearning.com/aasld.aspx Spontaneous portosystemic shunts (SPSS) are commonly observed in patients undergoing living donor liver transplantation (LDLT); however, their impact on the outcome after transplantation is unclear. We aimed to assess the type, size, and the effects of SPSS on outcomes after LDLT. A total of 339 LDLT recipients in a single institution were included. The type and diameter of the SPSS (splenorenal shunt [SRS], oesogastric shunt, and umbilical shun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
0
13
1
Order By: Relevance
“…Allard et al found that SPSS do not negatively affect the outcome after LDLT and suggested "do-nothing" approach in living donor LT. Furthermore, dissection of the spleen or ligation of the shunts could induce additional adverse events (18). Although Gomez Gavara et al found the incidences of post-LT HE and PVT were lower in the ligated SPSS group than those in nonligated SPSS group, they still supported the "do-nothing" idea in case of small size graft (split-liver living donor graft or small whole liver graft with low graft-to-body weight ratio) (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allard et al found that SPSS do not negatively affect the outcome after LDLT and suggested "do-nothing" approach in living donor LT. Furthermore, dissection of the spleen or ligation of the shunts could induce additional adverse events (18). Although Gomez Gavara et al found the incidences of post-LT HE and PVT were lower in the ligated SPSS group than those in nonligated SPSS group, they still supported the "do-nothing" idea in case of small size graft (split-liver living donor graft or small whole liver graft with low graft-to-body weight ratio) (19).…”
Section: Discussionmentioning
confidence: 99%
“…Although Gomez Gavara et al found the incidences of post-LT HE and PVT were lower in the ligated SPSS group than those in nonligated SPSS group, they still supported the "do-nothing" idea in case of small size graft (split-liver living donor graft or small whole liver graft with low graft-to-body weight ratio) (19). Only when portal flow is deemed insufficient either on the basis of visual examination or doppler ultrasonography (portal flow velocity <20 cm/s or portal flow <1 L/minute), the SPSS should be sought, isolated, and ligated after a positive clamping test (18). In case of spontaneous SRS, we could clamp the LRV on the left border of the IVC to test the effect of SRS on portal flow, in other case, the SPSS can be controlled directly.…”
Section: Discussionmentioning
confidence: 99%
“…91 However, there is debate as to whether to obstruct or not to obstruct such spontaneous portosystemic shunts after graft reperfusion. [92][93][94][95][96] In whole liver transplantation or pediatric LDLT, transplanted grafts could accommodate huge portal inflow and therefore shunts should be obstructed to prevent portal steal syndrome causing ischemic injuries to the grafts. In adult-to-adult LDLT, however, total obstruction of such shunts might cause excessive portal inflow and portal hypertension causing graft injuries, and preservation of them in turn might lead to portal steal phenomena and graft ischemia.…”
Section: Portosystemic Shuntmentioning
confidence: 99%
“…98,99 The Tokyo group recently reported that they perform neither obstruction of large portosystemic shunts nor splenectomy, under the use of large LDLT grafts >40% for GV/SLV, although the incidence of portal vein thrombosis after LDLT was high. 92 Kyushu group ligate large shunts to maintain adequate portal flow and to prevent the steal phenomenon as long as the portal pressure does not exceed 20 mm Hg after test clamping 94,100 (Figure 2). The important point in leaving large portosystemic shunts open is that only shunts connected to vena cava could be left open for possible interventional obstruction approach in case of post-transplant portal steal syndrome after LDLT.…”
Section: Portosystemic Shuntmentioning
confidence: 99%
“…Spontaneous portosystemic shunts (SPSS), which refer to the development of collateral vessels for diverting blood from splanchnic circulation to inferior vena cava, 1 are a common complication of portal hypertension in liver cirrhosis with a prevalence of 43–60% 2,3 . It is a main precipitating factor for hepatic encephalopathy (HE) and negatively affects the outcomes of patients with liver cirrhosis 4,5 . Except for gastroesophageal varices, which are the most widely studied type of SPSS, spontaneous splenorenal shunt (SSRS) is one of the most common types of SPSS, 6 which is defined as abnormal collateral vessels from splenic vein to renal vein 7 .…”
Section: Introductionmentioning
confidence: 99%